Mantras and Materialities: Saidaiji Order Kōmyō Shingon Practices - Quinter, David (Japanese journal of religious studies, 2018)
Mantra of Light (komyo shingon) practices have been among the most popular esoteric Buddhist rituals in Japan since the thirteenth century. Chinese scriptures recorded that reciting the mantra and distributing sand empowered by it could erase transgressions and ensure rebirth in the Pure Land. Subsequently, teachings on the significance of the sand empowered by the mantra received a strong boost from lectures and commentaries by Myoe (1173-1232), which many scholars have emphasized in assessing the mantra's spread. This article argues, however, that focus on the sand and such commentarial literature obscures another key to the mantra's popularization in medieval Japan: the annual Mantra of Light assemblies implemented by Eison (1201-1290) at Saidaiji in 1264. In particular, based on both premodern sources and ethnographic observations, the article investigates the Saidaiji order's use of contributor rosters for fundraising, recitation, and iconographic adornment to help illuminate the intertwined social, ritual, and material culture of the assemblies.